Gamifying Education: Teachers and Students Perceptions on Enhancing Motivation and Engagement - Anver Allie, Sabeehah; van Wyk, Mari; Moodley, Kimera (Papanda Publisher, 2025)
The widespread integration of digital technology in education, accelerated by the COVID-19 pandemic, has led to a shift in student preferences toward online learning. This poses a significant challenge for teachers to maintain student motivation and engagement in traditional classroom settings without risking a decline due to the ingrained reliance on virtual education methods. This study explores the dynamic integration of technology into daily educational practices, specifically through the lens of gamification, with a focus on teachers' and students' perceptions of utilising Book Widgets to augment teaching and learning experiences. Employing a qualitative approach and adopting a case study design, semi-structured interviews were conducted with 10 Grade 5 students from a girls-only private primary school in Saudi Arabia. Simultaneously, online questionnaires were distributed to teachers in Saudi Arabia using Book Widgets, through convenience and voluntary sampling. Thematic analysis, facilitated by the Atlas-ti Software, was employed to derive meaningful insights from the collected data. The research highlights the effectiveness of Book Widgets in boosting both intrinsic and extrinsic motivation among students, prompting teachers to strategically use Book Widgets as a tool for increased engagement and participation, particularly in primary school settings. Establishing Book Widgets as a valuable instrument for fostering motivation and engagement, the implications for optimising integration into educational practices to enhance student involvement further, are evident.